Economics of the public sector - "Stiglitz, Joseph E." (New York, 2000)
Professor Stiglitz builds on the book$1 (Bs classic strengths: an integrated approach to public economics, a readable and inviting style, and careful attention to real-world problems and applications.s
Keywords: Public finance-United States